STRATEGI DALAM MEMENUHI KEBUTUHAN HIDUP PADA RUMAH TANGGA PEMULUNG (Studi Kasus : Pemulung di Tempat Pembuangan Akhir Sampah Kelurahan Balai Gadang Kecamatan Koto Tangah Padang) - -, NESSA - (Pendidikan Sosiologi, 2014)
Informal sector is one alternative jobs for those who are not able to complete in the formal sector. Besides that the informal sector is also easy to get into for anyone who wants it in the sense that the informal sector does not require any special skills compared to the formal sector. One example of workin the formal sector is collecting used goods, or the so-called âscavengersâ. Scavenger often synonymous with the word âpoorâ which simply means one who is always in touch with the state of economic deprivation and social life are alwaysin isolate or not noticed. As well as scavenger at Landfill Village Balai Gadang Subdistrict Koto Tangah Padang. The purpose of this study was to describe how the strategies to meet the needs of household living on a scavenger at landfill village balai gadang subdistrict koto tangah padang.The theory used in this study were derived from the theory of social action according to Max Weber, sosial action is an act of individuals throughout the action has meaning for him and directed at another person. The study used a qualitative appoach and type of research is deskriptive type of analysis. Informants of the studi are scavenger at landfill village balai gadang subdistrict koto tangah padang. Selection techniques using purposive sampling who were 8 households scavengers. Data colected through obervation, interviews and document with data reduction step, clarification of data,and conclusions or data verification.Based on research results that there scavenger in landfills (TPA) of waste village hall has a large sieve strategies in meeting unmet needs if that is the way: 1. The home gardens, 2. Do additional work, 3. Involving members of the houshold, 4. borrow 5. Pressing household, 6. saving